Private-label branding and willingness to pay: evidence from an auction experiment - Kandapa Thanasuta (2019)
© 2018 Informa UK Limited, trading as Taylor & Francis Group. The competitive pricing of private-label brands is a strategy used to gain a competitive advantage. Notwithstanding the introduction of many private-label brands–i.e. private-label brands with a name identical to that of a firm (own-name brands) and private-label brands with a name distinctive from that of a firm (other-name brands)–that compete with national brands, identifying equitable prices that reflect brand value remains difficult. This study aims to determine the appropriate price of private-label brands by measuring consumers’ willingness to pay. An experimental auction method measures ‘actual’ willingness to pay in a non-hypothetical setting. The study was conducted in Thailand, which has the lowest price discrepancy between national brands and private-label brands. The results show that the willingness of consumers to pay for both types of private-label brands is higher than that for un-branded products. However, there is no significant difference in the premium between own-name and other-name private-label brands. Unlike leading and second tier national brands, consumers are willing to pay a discounted price for both own-name and other-name private-label brands; for the latter, they are willing to pay a more steeply discounted price. The finding of this study regarding the amount that consumers are willing to pay for an own-name private-label brand is consistent with the current market price strategy, whereas the current market price strategy for other-name private labels is inconsistent with the amount participants are willing to pay. The study shows that to appropriately price their products in a manner that yields the highest returns, retailers must determine how much consumers are willing to pay.